Eccrine Sweat Gland and Its Regeneration: Current Status and Future Directions - Lin, Yao; Chen, Liyun; Zhang, Mingjun; Xie, Sitian; Du, Lijie; Zhang, Xiang; Li, Haihong (Frontiers in Cell and Developmental Biology, 2021)
Eccrine sweat glands (ESGs) play an important role in temperature regulation by secreting sweat. Insufficiency or dysfunction of ESGs in a hot environment or during exercise can lead to hyperthermia, heat exhaustion, heatstroke, and even death, but the ability of ESGs to repair and regenerate themselves is very weak and limited. Repairing the damaged ESGs and regenerating the lost or dysfunctional ESGs poses a challenge for dermatologists and bum surgeons. To promote and accelerate research on the repair and regeneration of ESGs, we summarized the development, structure, and function of ESGs, and current strategies to repair and regenerate ESGs based on stem cells, scaffolds, and possible signaling pathways involved.